Effect of methylation of ionic liquids on the gas separation performance of ionic liquid/metal–organic framework composites. Issue 44 (25th October 2018) - Nozari, Vahid; Zeeshan, Muhammad; Keskin, Seda; Uzun, Alper
Abstract : [BMIM][PF6 ] and its methylated form, [BMMIM][PF6 ] were incorporated into CuBTC to examine the effect of methylation of ionic liquids (ILs) on the gas separation performance of the corresponding IL/metal–organic framework (MOF) composites. Abstract : 1- N -Butyl-3-methylimidazolium hexafluorophosphate, [BMIM][PF6 ], and its methylated form, 1- N -butyl-2, 3-dimethylimidazolium hexafluorophosphate, [BMMIM][PF6 ], were incorporated into CuBTC to examine the effect of methylation of ionic liquids (ILs) on the gas separation performance of the corresponding IL/metal–organic framework (MOF) composites. Spectroscopic analysis revealed that the interactions of the methylated ILs with CuBTC were weaker compared to those of its non-methylated counterpart. Gas uptake measurements illustrated that this difference in the interactions influences the gas separation performance of the composites. Accordingly, the CO2 /N2 : 15/85 and CH4 /N2 : 50/50 selectivities increased by 37% and 60% for [BMMIM][PF6 ]/CuBTC and 34% and 50% for [BMIM][PF6 ]/CuBTC, respectively, compared to the corresponding selectivities of pristine CuBTC at 1000 mbar. The results revealed another structural parameter controlling the performance of the IL/MOF composites, a novel type of material with rapidly expanding application areas.